2002
DOI: 10.1002/cne.10155
|View full text |Cite
|
Sign up to set email alerts
|

Synaptic organization of the mushroom body calyx in Drosophila melanogaster

Abstract: The calyx neuropil of the mushroom body in adult Drosophila melanogaster contains three major neuronal elements: extrinsic projection neurons, presumed cholinergic, immunoreactive to choline acetyltransferase (ChAT-ir) and vesicular acetylcholine transporter (VAChT-ir) antisera; presumed gamma-aminobutyric acid (GABA)ergic extrinsic neurons with GABA-like immunoreactivity; and local intrinsic Kenyon cells. The projection neurons connecting the calyx with the antennal lobe via the antennocerebral tract are the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
291
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 263 publications
(319 citation statements)
references
References 87 publications
(95 reference statements)
27
291
1
Order By: Relevance
“…Second, injection of MEC into the calyces also completely impaired conditioning. Since Kenyon cells receive cholinergic inputs from projection neurons in the calyces (Yasuyama et al, 2002), the neurons affected were no doubt Kenyon cells. We thus suggest that the association occurs in MEC-sensitive…”
Section: Major Findingsmentioning
confidence: 99%
See 2 more Smart Citations
“…Second, injection of MEC into the calyces also completely impaired conditioning. Since Kenyon cells receive cholinergic inputs from projection neurons in the calyces (Yasuyama et al, 2002), the neurons affected were no doubt Kenyon cells. We thus suggest that the association occurs in MEC-sensitive…”
Section: Major Findingsmentioning
confidence: 99%
“…We evaluated localization of the injected drug by observing the distribution of co-injected (Yasuyama et al, 2002).…”
Section: Localization Of Injected Solutionmentioning
confidence: 99%
See 1 more Smart Citation
“…1B), and comprise many thousands of synaptic complexes, called microglomeruli (Yasuyama et al, 2002) that are revealed by phalloidin staining (Fig. 1C and inset).…”
Section: General Organization and Concentric Zonation Of The Calycesmentioning
confidence: 99%
“…After processing in the antennal lobes, olfactory information is relayed by PNs to the mushroom bodies and the protocerebrum. Like other excitatory neurons in the insect central nervous system (CNS), most of these PNs are cholinergic [15] .…”
mentioning
confidence: 99%